Drivers of production performance and profitability of the livestock sector in the less favoured areas of England: the impact of distance, financial dependency and machinery. - Vittis, Goerge; Gadanakis, Yiorgos; Mortimer, Simon (My University, 2017)
Agricultural production in Less Favoured Areas (LFAs) is more difficult since farming faces certain natural challenges. Such barriers may lead to a reduction or suspension of agricultural activities resulting in a series of environmental pressures such as loss of biodiversity and land abandonment. Thus, maintenance and sustainable development of the agricultural systems within the LFAs emerges as a prerequisite for preserving the environment of the English uplands. Towards this direction, the identification of factors that enhance or hinder agricultural performance in the LFAs is required to enable the design of future development strategies and policy interventions. Principal Component Analysis (PCA) is employed here to group into core underlying factors variables related to climate and landscape characteristics as well as management choices. Multiple Linear Regression (MLR) was then used to test the explanatory power of the independent variables in explaining variations in business performance. Financial and physical data used in the study were derived from the Farm Business Survey dataset whereas climate variables were obtained from the Met Office climate monitoring. The results provide evidence to support that remoteness, climate, financial aid and technological level are drivers of good performance of the grazing livestock systems. Hence, the results suggest areas of policy-making interventions in the livestock sector of the LFAs that aim towards sustainable intensification of production.
Keywords: Less Favoured Areas; Grazing Livestock Systems; English uplands; Sustainable development; Spatial analysis